The implications of the financial action task force findings on south africa’s national security - Mdawo, Lesego Wilson (University of the Witwatersrand, Johannesburg, 2024)
In February 2023, the Financial Action Task Force (FATF) added South Africa to the list of jurisdictions under increased supervision (greylist) due to substantial deficiencies in its monitoring and combating money laundering and the financing of organisations that may pose a threat to national and global security. The FATF is an inter-governmental body responsible for coordinating global efforts to combat money laundering, financing of terrorism, and proliferation financing (AML/CFT). It establishes global standards to mitigate against risks, and conducts assessments on countries to check effectiveness of their regimes. This research sought to analyse the implications of the FATF findings on South Africa’s national security. The research analysed the implications against political and economic security of South Africa, key tenets of national security. Through document analysis and semi-structured interviews, the research found that the Mutual Evaluation conducted by FATF was a fair reflection of South Africa’s AML/CFT regime. It identified structural weaknesses in South Africa’s law enforcement agencies and legislative framework. Recommendations by FATF have far reaching economic and political implications which has consequences for the country’s national security. The response by government to address FATF findings has been impressive, leading to better coordination and increased political will in strengthening South Africa’s AML/CFT regime, and getting off the greylist
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; FATF; National security; Political security; Economic security; SDG-8: Decent work and economic growth